Validation of Resilience Scale (CD-RISC) in elite athletes through a structural equation model (Validación de la Escala de Resiliencia (CD-RISC) en deportistas de élite a través de un modelo de ecuaciones estructurales) - Olmo Extremera, Marta; Olmedo Moreno, Eva; Cepero González, Mar; Zurita Ortega, Felix; Padial Ruz, Rosario (Retos, 2017)
Resilience is a psychological characteristic that encourages positive adaptation in the face of adversity (Connor & Davidson, 2003; Grotberg, 2001; Wagnild & Young, 1990). It has seldom been studied within the field of sports but, in the last years the studies began to be more common (Fletcher & Sarkar, 2012; Galli & Vealey, 2012; García- Secades et al., 2015). This work has as purposes, to adapt the resilience scale (CD-RISC) for the sport field, to confirm its psychometrics properties and to analyses, validation its internal consistency in a population of elite athletes in different sports. The scale was administered to a sample of 287 athletes, 76.7% male and 23.3% female, determined by four levels of competition; 21.5% professionals, 21.3% semi-professionals, 43.9% amateur and 9.8% enthusiastic. It was an analysis based on structural equations modelling (SEM) encompassed within confirmatory factor analysis (CFA) and its internal consistency (Cronbach's Alpha). The results verified that the modelling of structural equation, the model for measuring the questionnaire and the covariant structure of the responses obtained have a good fit. Thus, the CD-RISC scale has shown itself to be a reliable and valid tool for measuring the resilience of elite athletes and it can also be used to measure psychological parameters related to the field of sports.Resumen. La resiliencia es una característica psicológica que permite una adaptación positiva ante la adversidad (Connor & Davidson, 2003; Grotberg, 2001; Wagnild & Young, 1990). Sus estudios en el campo deportivo no han sido muy numerosos, aunque en los últimos años esta tomando fuerza en esta area (Fletcher & Sarkar, 2012; Galli & Vealey, 2012; García- Secades et al., 2015). El trabajo que se presenta tiene como objetivos adaptar al campo deportivo la escala de resiliencia (CD-RISC), confirmar sus propiedades psicométricas, analizar y validar su consistencia interna en una población de atletas de élite en diferentes deportes. La escala fue aplicada a una muestra de 287 atletas, 76,7% hombres y 23,3% mujeres diferenciados por cuatro niveles de competición; 21,5% profesionales, 21,3% semi-profesionales, 43,9% amateur y 9,8% aficionados. Se utilizó un análisis basado en un modelo de ecuaciones estructurales (SEM) circunscritos a un análisis de confirmación de los factores (CFA) y su consistencia interna (Alfa de Cronbach). Los resultados verificaron que el modelo de ecuaciones estructurales, la mediación del cuestionario y la estructura covariante de las respuestas obtenidas tienen un buen ajuste. Por tanto, la escala CD-RISC ha demostrado ser una herramienta confiable y válida para medir la capacidad de resiliencia de los deportista de élite pudiendo ser utilizada para medir los parámetros psicológicos relacionados con el campo deportivo.